Pengembangan Aplikasi Mobile Phone Kosakata Bahasa Inggris Untuk Siswa SD Di Papua - Sampebua, Mingsep Rante; Tanjung, Rosye H. R; Sampebua, Abigael (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The low level of student interest and the ability of Papua Abepura Adventist elementary school students in understanding and memorizing English vocabulary requires innovative learning media. The purpose of this research is to develop mobile phone-based English vocabulary learning media applications. English vocabulary learning applications can improve English vocabulary mastery for elementary school students, increase student motivation and interest in learning vocabulary, student-centered learning, trigger student creativity, effectiveness, build student independence in learning vocabulary, and the learning process can be done whenever and wherever students want to learn. This is expected to change the mindset and culture of using mobile phones for elementary school students in Papua so that they can be used properly and efficiently for learning English vocabulary. The application development method uses the waterfall which includes five stages, namely identification of user needs for learning English vocabulary, analysis, design, implementation, and testing